Silver(I)‐Catalyzed Route to Pyrroles: Synthesis of Halogenated Pseudilins as Allosteric Inhibitors for Myosin ATPase and X‐ray Crystal Structures of the Protein–Inhibitor Complexes1. Issue 21 (28th May 2014) - Martin, René; Risacher, Célia; Barthel, André; Jäger, Anne; Schmidt, Arndt W.; Richter, Sabine; Böhl, Markus; Preller, Matthias; Chinthalapudi, Krishna; Manstein, Dietmar J.; Gutzeit, Herwig O.; Knölker, Hans‐Joachim
Abstract: The pentahalogenated 2‐arylpyrrole‐type alkaloids pentabromopseudilin and pentachloropseudilin represent a new class of isoform‐specific allosteric inhibitors of myosin ATPase. Herein, we describe an application of the silver(I)‐catalyzed cycloisomerization of N ‐(homopropargyl)toluenesulfonamides to the total syntheses of these natural products and several non‐natural analogues. Moreover, we examine the inhibitiory effect of pentahalogenated pseudilins on myosin ATPase activity. Abstract : The alkaloids pentabromopseudilin and pentachloropseudilin represent a new class of isoform‐specific allosteric inhibitors of myosin ATPase. Herein, we describe an application of the silver(I)‐catalyzed cycloisomerization of N ‐(homopropargyl)toluenesulfonamides to the syntheses of these alkaloids and their non‐natural analogues as well as a study of their inhibition of myosin ATPase activity.